Comparison of Oral Versus Vaginal Misoprostol for Induction of Labour at Term - Zoqeen Akhtar, Shabnam Tahir Saleem*, Farzana Lateef (Journal of Rawalpindi Medical College, 2010)
Background: To compare the efficacy and safety of oral versus vaginal administration of Misoprostol for induction of labour at term. Methods: In this interventional study primigravida were assigned in two groups; A and B, using non-probability convenient sampling technique. Group-A (n=50) had Misoprostol orally, while group-B (n=50) received the drug by vaginal route. Dosage was 100 μg four hours apart in group-A and six hours apart in group-B. Maximum of four doses were given. Main outcome measures of study were labour-induction interval, labour-delivery interval, mode of delivery, neonatal outcome and feto-maternal complications. Results: The mean dosage requirement for induction of labour in groups A and B was 2.1±1.1 and 2.4±1.8 (p-0.23) respectively. Mean labour-induction interval in group A and B were 7.5±4.2 and 7.3±4.1 (p-0.87) hours respectively, which is not significant statistically. Mean labour delivery interval was shorter in vaginal group (4.9±2.7 hours) versus oral group(6.0±2.2) hours (p-0.04). Need for Oxytocin augmentation was less in vaginal group (21%) versus oral group (68%) (p-0.009). There was no statistical difference between the groups with respect to mode of delivery and neonatal outcome. The incidence of hyper-stimulation was similar in both groups. Conclusion:Misoprostol is a cost effective alternate for induction of labour. Misoprostol through vaginal route results in successful cervical ripening, less need for oxytocin and shorter time to delivery with acceptable safety profile.